1997
DOI: 10.1210/jc.82.2.607
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ovine Corticotropin-Releasing Hormone Injection and Desmopressin Coadministration on Galanin and Adrenocorticotropin Plasma Levels in Normal Women

Abstract: The neuropeptide galanin (GAL) has been shown to be located in the pituitary gland and to modulate the secretion of several pituitary hormones. In the human pituitary, GAL is almost exclusively located within corticotrophs. We examined whether GAL is secreted from corticotrophs in response to stimuli that induce ACTH release. Plasma levels of GAL and ACTH were evaluated in six healthy female subjects in the follicular phase of the menstrual cycle after the following treatments: 1) ovine CRH (oCRH) injection du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Compared with our previous results (8), the data obtained in a larger group of normal individuals con®rm the consistent lack of signi®cant ACTH/cortisol responses to this peptide in this population (6,15,21) ± a feature that might be a consequence of an insuf®cient expression of V3 receptors in normal corticotrophs. This consideration prompted us to evaluate whether the desmopressin challenge might be of value in the postoperative follow-up of patients with Cushing's disease after successful surgery.…”
Section: Journal Of Endocrinology (2000) 143supporting
confidence: 67%
“…Compared with our previous results (8), the data obtained in a larger group of normal individuals con®rm the consistent lack of signi®cant ACTH/cortisol responses to this peptide in this population (6,15,21) ± a feature that might be a consequence of an insuf®cient expression of V3 receptors in normal corticotrophs. This consideration prompted us to evaluate whether the desmopressin challenge might be of value in the postoperative follow-up of patients with Cushing's disease after successful surgery.…”
Section: Journal Of Endocrinology (2000) 143supporting
confidence: 67%
“…It has been reported that desmopressin test is able to differentiate patients with Cushing's disease from the majority of normal subjects and patients with obesity, depression or pseudo-Cushing states [14,16,17,[22][23][24]. It has been reported that desmopressin test is able to differentiate patients with Cushing's disease from the majority of normal subjects and patients with obesity, depression or pseudo-Cushing states [14,16,17,[22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…The conclusion from previous studies of DDAVP‐induced ACTH release is that DDAVP is not a stimulant of the pituitary‐adrenal system in health (Malerbi et al ., 1996; Ceresini et al ., 1997). This has been used as a basic premize in subsequent studies (Newell‐Price et al ., 1997).…”
Section: Discussionmentioning
confidence: 99%
“…DDAVP induced ACTH and cortisol release has been shown in recent studies to reliably distinguish between Cushing's disease patients and subjects with depression (Malerbi et al ., 1996) and also to have potential application in the postoperative follow‐up of Cushing's patients (Colombo et al ., 1997). DDAVP can augment the pituitary‐adrenal response to CRH in healthy subjects (Ceresini et al ., 1997). It has proved to be a safe and well tolerated substance.…”
mentioning
confidence: 81%